BALANCED SCORECARD SEBAGAI INDIKATOR PENGELOLAAN SUMBER DAYA ALAM - BASTIAN, ANNEKE (Universitas Katolik Widya Mandala Surabaya, 2012)
An increasingly competitive business environment requires companies to be managed professionally. Companies must be able to prepare strategies and refine the vision in order to survive and win the competition. The concept of the balanced scorecard is expected to translate vision and strategy. Selection of the vision, mission, and the right business strategy will facilitate the company achieve its goals if it is supported by an element that is, its natural resources. Natural resources are managed and conserved in order to be ustainable (sustainability) so that natural resources can be passed on to future generations. Natural resource management focused on the human or the community, economic actors, and the strategy of what needs to be taken so that natural resources be utilized optimally. The results of the discussion has concluded that the management of natural resources carried out by applying the principle of balanced scorecard and is based on how the vision, mission and strategy in the future the company is expected to be truly able to fit well integrated in the company's business activities. Natural resource management should be undertaken in stages and gradually realize that its utilization can be as effective as possible.